2019
DOI: 10.1016/j.str.2018.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Intradomain Interactions in an NMDA Receptor Fragment Mediate N-Glycan Processing and Conformational Sampling

Abstract: Summary The structural and functional roles of highly conserved asparagine-linked (N)-glycans on the extracellular ligand-binding domain (LBD) of the N-methyl-D-aspartate receptors (NMDAR) are poorly understood. We applied solution- and computation-based methods that identified N-glycan mediated intradomain and interglycan interactions. NMR spectra of the GluN1 LBD showed clear signals corresponding to each of the three N-glycans and indicated the reducing end of glycans at N440 and N771 potentially contacted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…Further, iGluRs including GluK3, are extensively N-glycosylated which likely imparts an additional level of regulation of their functions. These glycans have been reported to affect the trafficking, gating properties 16–18 and assembly of iGluRs 1924 . They likely affect receptor functions by interactions with other synaptic proteins or by mediating inter- and intra-domain interactions in iGluRs 19 affecting receptor functionality 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Further, iGluRs including GluK3, are extensively N-glycosylated which likely imparts an additional level of regulation of their functions. These glycans have been reported to affect the trafficking, gating properties 16–18 and assembly of iGluRs 1924 . They likely affect receptor functions by interactions with other synaptic proteins or by mediating inter- and intra-domain interactions in iGluRs 19 affecting receptor functionality 20 .…”
Section: Introductionmentioning
confidence: 99%
“…The role of N-glycans of GluN1, an NMDA-type glutamate receptor subunit, has been extensively investigated using nuclear magnetic resonance and molecular dynamics analyses. N-glycans on the ligand-binding region of GluN1 have been shown to directly interact with nearby peptides and N-glycans, maintaining its structure and regulating its glycin-binding ability [28,29]. Moreover, since AMPARs are tetrameric ion channels, stoichiometry studies are needed to determine how many and which N-glycans of the four subunits are necessary to maintain AMPAR function.…”
Section: Discussionmentioning
confidence: 99%
“…Inverse distances of glycan residues to vicinal hexoses and amino acids (with hydrogen bond donating/accepting side chains) were chosen as features for the MSMs, as described before [13,14]. Each glycan was individually analyzed using a site-specific choice of considered neighboring glycans and protein surface residues for the (inverse) distance calculations (table EV1).…”
Section: Markov State Modelingmentioning
confidence: 99%
“…It is however the single high-mannose type UMOD glycan that mediates encapsulation and aggregation of uropathogens by UMOD filaments via interactions with mannoside-specific pilus lectins from the pathogens [12]. In addition, the rise of computational glycobiology allowed the simulation of glycan-protein interactions [13,14] and indicated that these interactions could reduce the accessibility of the glycan to glycan-processing enzymes [15]. Consequently, glycan-protein interactions are considered a major determinant of N-glycan microheterogeneity [15,16].…”
Section: Introductionmentioning
confidence: 99%